2022
DOI: 10.1142/s0218625x22501098
|View full text |Cite
|
Sign up to set email alerts
|

WATER-BASED ACRYLIC POLYMER/ZnO–Ag NANOCOMPOSITE COATING FOR ANTIBACTERIAL APPLICATION

Abstract: The goal of this work is to study the antibacterial activity of acrylic polymer/ZnO–Ag nanocomposite coating. First, in the presence of UV light ([Formula: see text][Formula: see text]nm), Ag nanoparticles (NPs; derived from AgNO3 precursor) were photoreduced and deposited on the surface of nano-ZnO. Field emission scanning electron microscope (FE-SEM) images indicated that the AgNPs (5–15[Formula: see text]nm) were deposited on the surface of nano-ZnO (20–40[Formula: see text]nm). These ZnO–Ag nanohybrids (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…and 41% of increase for ZnO@Ce 3+ (upto 117 L/mil.). This finding is coherent with the previous works on the UV-cured acrylate epoxy coating (with ZnO@Ag nanoparticles, Nguyen et al , 2022a) and the acrylic polymer coatings (with SiO 2 @Ag nanoparticles, Le et al , 2019; or with ZnO@Ag nanoparticles, Vu et al , 2022). These nanoparticles could reduce the porosity of the coating, not only by taking place in the hollows, pinholes or voids, but also by serving as bridges to interconnect the coating matrices.…”
Section: Resultssupporting
confidence: 92%
“…and 41% of increase for ZnO@Ce 3+ (upto 117 L/mil.). This finding is coherent with the previous works on the UV-cured acrylate epoxy coating (with ZnO@Ag nanoparticles, Nguyen et al , 2022a) and the acrylic polymer coatings (with SiO 2 @Ag nanoparticles, Le et al , 2019; or with ZnO@Ag nanoparticles, Vu et al , 2022). These nanoparticles could reduce the porosity of the coating, not only by taking place in the hollows, pinholes or voids, but also by serving as bridges to interconnect the coating matrices.…”
Section: Resultssupporting
confidence: 92%
“…24,25 For UV-curable systems, inuence of certain additives on their photocrosslinking are reported. 26 Recently, Nguyen et al 27,28 reported the synthesis and antibacterial activity of ZnO-Ag nanohybrids. The authors found the good antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria, even at low content (<40 mg mL À1 ) with the higher inhibition areas.…”
Section: Introductionmentioning
confidence: 99%
“…12,[18][19][20][21][22] For the crosslinking of thermoset resin system, the presence of additives can affect to the components of paint formulations. [23][24][25][26][27][28][29][30][31][32][33] Regarding the epoxy nanocomposite, nanollers could act as a bridge for the interconnected molecules, and thus reduce the free volume and increase the crosslinking density. 24,25 For UV-curable systems, inuence of certain additives on their photocrosslinking are reported.…”
Section: Introductionmentioning
confidence: 99%